Un sindicato siderúrgico : desarrollo y declive de una propuesta gremial para los trabajadores de SOMISA (Argentina, 1965-1973) - César Mónaco (Les Cahiers ALHIM)
The paper aims to account for the most relevant aspects of the attempt to establish a union in the state-owned steel Sociedad Mixta Siderurgia Argentina (SOMISA) from the mid-sixties and the early years of the next decade. This proposal was intended to dissociate the activity of the steelworks metallurgical branch. Its emergence and development came under a special period in the history of Argentina, distinguishable in at least two aspects. At first term, in the context of boosting of heavy industrial activity. At its second edition, it was into a background of crisis of major unions and a widespread climate of rank and file rebellion. That’s when, in rejecting of the representation of the Unión Obrera Metalúrgica –union of the industry-, the project was accompanied both leftists as large swathes of workers unhappy with their union representation.